Comparison of Fracture Strength of Endodontically Treated Teeth Restored with Two Different Cast Metallic Post Systems - Borhan Haghighi Z; Pahlavanpour Fard Jahromy AM (Shiraz University of Medical Sciences, 2014)
Statement of Problem: Endodontically treated teeth are more prone to fracture. The post and core are often used to provide the necessary retention for prosthetic rehabilitation. Objectives: The purpose of this study was to: 1) compare the fracture strength of endodontically treated teeth restored either with Nickel-Chromium (Ni- Cr) post or Non- Precious Gold-color alloy (NPG) post compared to the control group and 2) evaluate the fracture site in each group. Materials and Methods: In this experimental study, endodontic treatment was carried out for 45 extracted maxillary premolars. The specimens were divided into 3 groups (n=15). Group1: restored with NPG post and core, group2: restored with Ni-Cr post and core, and group 3, no post and core were used after endodontic treatment and the access cavity was filled with amalgam. Failure force was recorded in Newton when root or remaining coronal structure fracture was occurred. Data were analyzed using one-way analysis of variance (ANOVA), Student t-test and Tukey HSD test to compare the three groups. Results: There was a statistically significant difference among all groups (P<0.05). Fracture resistance of the teeth restored by NPG posts was significantly higher than those restored by Ni- Cr (P<0.001). Results showed that the fracture mainly occurred in the root of the teeth restored with Ni- Cr and NPG post while fractures occurred in the core portion of the teeth restored with amalgam. Conclusions: The findings of the present study indicated that the fracture strength of the teeth without using cast post and core was significantly lower than the teeth restored with cast post and core. Also the teeth restored by NPG post had a significantly higher fracture resistance than Ni-Cr posts.